Bringing Tegenaria boitanii stat. rev. back to life with a review of the Tegenaria percuriosa-complex (Araneae: Agelenidae), description of a new species and insight into their phylogenetic relationships and evolutionary history. Issue 1 (31st December 2022) - Dimitrov, Dragomir; Bolzern, Angelo; Arnedo, Miquel
Abstract : The funnel web spiders (Agelenidae) are a diverse and taxonomically challenging worldwide distributed family. The genus Tegenaria Latreille, 1804, includes more than 100 valid species, mostly circumscribed to Europe and western Asia, although some species may have been subsequently introduced to other regions by anthropogenic action. Here we revise and investigate phylogenetic relationships of a group of morphologically similar species from the south-western Black Sea region and Anatolia. We remove the species Tegenaria boitanii Brignoli, 1978 stat. rev. and Tegenaria bithyniae Brignoli, 1978 from synonymy of Tegenaria percuriosa Brignoli, 1972 . Tegenaria boitanii stat. rev. is restored as a valid species, re-described and re-diagnosed, and T. bithyniae syn. nov. is placed as its junior synonym. We also provide an updated diagnosis for T. percuriosa, describe a new species, Tegenaria euxinica Dimitrov sp. nov. from the mesophilic beech forests ( Fagus orientalis ) in Bulgaria, and review the members of T. percuriosa complex. We provide new photographs for selected species, and a map of the updated distribution ranges of all the species in the complex. The phylogenetic position and internal structure of T. percuriosa species-complex is investigated by combining available morphological and molecular (target sequencing) data with new data from the species of interest. Finally, we propose to test in future studies the hypothesis that major climatic changes during the Miocene drove diversification of the group and imprinted its biogeography. http://zoobank.org/urn:lsid:zoobank.org:pub:08A77B59-ACFE-4C16-BBCB-BC45BE981360